Medicinal Chemistry of P2X Receptors: Allosteric Modulators - E. Muller, Christa (Current Medicinal Chemistry, 2015)
P2X receptors are trimeric ligand-gated ion channels whose potential as novel drug targets for a number of diseases has been recognized. They are mainly involved in inflammatory processes, including neuroinflammation, and pain sensation. The orthosteric binding site is lined by basic amino acid residues that bind the negatively charged agonist ATP. Therefore it is not easy to develop orthosteric ligands that possess drug-like properties for such a highly polar binding site. However, ligand-gated ion channels offer multiple additional binding sites for allosteric ligands, positive or negative allosteric modulators enhancing or blocking receptor function. So far, the P2X3 (and P2X2/3), as well as the P2X7 receptor subtype have been the main focus of drug development efforts. A number of potent and selective allosteric antagonists have been developed to block these receptors. We start to see the development of novel allosteric ligands also for the other P2X receptor subtypes, P2X1, P2X2 and especially P2X4. The times when only poor, non-selective, non-drug-like tools for studying P2X receptor function were available have been overcome. The first clinical studies with allosteric P2X3 and P2X7 antagonists suggest that P2X therapeutics may soon become a reality.
Keywords: P2X1